Desain Pendidikan Multikultural di Pondok Pesantren Salaf Kauman Alhasani Allathifi Bondowoso - Suheri Suheri; Yeni Tri Nurrahmawati (Proceedings of Annual Conference for Muslim Scholars, 2018)
Islam has come up with values ​​that uphold peace, Islam in practice teaches common attitudes with diversity, and uses even requires people to contribute positively within the context of the diversity, even in the view of Islam, the grace and fitrah that must be preserved not to be debated and disputed. This research produces research on the model of education in salaf pesantren with heterogeneous students by presenting models, methods, learning strategies that have the content of multicultural education. This is based on the proposition that multicultural education should be approached holistically and integratively. This research involves several important things from pesantren such as tradition, habbitus, understanding and implementation of the values ​​of multiculturalism articulated in curriculum form and the learning and life of santri in the application of multicultural education. The pesantren studied has unique and unique vision and meaning unique to multiculturalism, yet still requires appropriate strategies and programs for the same purpose. Thus the culture of pesantren and tradition becomes a strong capital in developing multiculturalism by not distinguishing differences in the background of others. The results of these findings can be prototypes of cultural education models through the integration of religious values ​​and local values ​​in the context of cultural pluralism and serve as a reference for education outside of pesantren that still upholds bulkheads and intellectual egoism.